Notas sobre el derecho a la información y a la transparencia como herramientas para el combate a la corrupción en el estado constitucional - Uribe Arzate, Enrique (2023)
This article presents the crisis of the model of the rule of law and the urgent need to reposition it within the paradigm of the constitutional state. The authors state that the model of the rule of law must be overcome by the constitutional principle, according to which the governed can do everything that the law prohibits, and what the Constitution allows them to do. This paper shows the need for providing society with legal instruments that enable it to exercise control over those who are entrusted with the authority of the state; this control must be a judicial review of the constitutional validity of acts and rules. In this context, the authors emphasize that the right to information is the most effective tool for the constr uction of a democratic and constitutional state.